Encephalitis as a neurological complication of COVID‐19: A systematic review and meta‐analysis of incidence, outcomes, and predictors - Siow, Isabel; Lee, Keng Siang; Zhang, John J. Y.; Saffari, Seyed Ehsan; Ng, Adeline (European journal of neurology, 2021)
Background and purpose Although COVID‐19 predominantly affects the respiratory system, recent studies have reported the occurrence of neurological disorders such as stroke in relation to COVID‐19 infection. Encephalitis is an inflammatory condition of the brain that has been described as a severe neurological complication of COVID‐19. Despite a growing number of reported cases, encephalitis related to COVID‐19 infection has not been adequately characterised. To address this gap, this systematic review and meta‐analysis aims to describe the incidence, clinical course, and outcomes of patients who suffer from encephalitis as a complication of COVID‐19. Methods All studies published between 1 November 2019 and 24 October 2020 that reported on patients who developed encephalitis as a complication of COVID‐19 were included. Only cases with radiological and/or biochemical evidence of encephalitis were included. Results In this study, 610 studies were screened and 23 studies reporting findings from 129,008 patients, including 138 with encephalitis, were included. The average time from diagnosis of COVID‐19 to onset of encephalitis was 14.5 days (range = 10.8–18.2 days). The average incidence of encephalitis as a complication of COVID‐19 was 0.215% (95% confidence interval [CI] = 0.056%–0.441%). The average mortality rate of encephalitis in COVID‐19 patients was 13.4% (95% CI = 3.8%–25.9%). These patients also had deranged clinical parameters, including raised serum inflammatory markers and cerebrospinal fluid pleocytosis. Conclusions Although encephalitis is an uncommon complication of COVID‐19, when present, it results in significant morbidity and mortality. Severely ill COVID‐19 patients are at higher risk of suffering from encephalitis as a complication of the infection.